Analisis Wacana Pesan Dakwah Dalam Film Negeri 5 Menara - Muhammad Rizal Fadillah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
Da'wah is an activity that calls, invites or calls others to obey the teachings of Allah SWT in accordance with the lines of aqidah, shari'ah and Islamic morals. In this context, da'wah requires media as a means used to convey da'wah material, for that there needs to be a revitalization of da'wah media that is not only fixated on traditional media. One of the contemporary da'wah media today is making films that carry da'wah messages. Film Negeri 5 Menara is a film that tells the story of the struggle of the students who are framed in their friendship. Overall, the film shows the values ​​of Islamic life that are accommodated in the da'wah space, such as showing the importance of hard work, enthusiasm, sincerity and sincerity. Da'wah and cinema actually need each other. This is of course understandable, considering the population of Muslims in Indonesia is so dominant that the public can be more open-minded that films do not always have to show action and comedy scenes, but many da'wah messages that can be taken in a wrapped film. with elements of da'wah that can be a good and interesting spectacle.